Cerebral Microstructural Alterations in Patients With Early Parkinson’s Disease Detected With Quantitative Magnetic Resonance Measurements - Klietz, Martin; Elaman, M. Handan; Mahmoudi, Nima; Nösel, Patrick; Ahlswede, Mareike; Wegner, Florian; Höglinger, Günter U.; Lanfermann, Heinrich; Ding, Xiao-Qi (Frontiers in Aging Neuroscience, 2021)
Objective: Parkinson’s disease (PD) is the second most common neurodegenerative disease in the elderly. In early stages of PD, patients typically display normal brain magnet resonance imaging (MRI) in routine screening. Advanced imaging approaches are necessary to discriminate early PD patients from healthy controls. In this study, microstructural changes in relevant brain regions of early PD patients were investigated by using quantitative MRI methods. Methods: Cerebral MRI at 3T was performed on 20 PD patients in early stages and 20 age and sex matched healthy controls. Brain relative proton density, T1, T2, and T2′ relaxation times were measured in 14 regions of interest (ROIs) in each hemisphere and compared between patients and controls to estimate PD related alterations. Results: In comparison to matched healthy controls, the PD patients revealed decreased relative proton density in contralateral prefrontal subcortical area, upper and lower pons, in ipsilateral globus pallidus, and bilaterally in splenium corporis callosi, caudate nucleus, putamen, thalamus, and mesencephalon. The T1 relaxation time was increased in contralateral prefrontal subcortical area and centrum semiovale, putamen, nucleus caudatus and mesencephalon, whereas T2 relaxation time was elevated in upper pons bilaterally and in centrum semiovale ipsilaterally. T2′ relaxation time did not show significant changes. Conclusion: Early Parkinson’s disease is associated with a distinct profile of brain microstructural changes which may relate to clinical symptoms. The quantitative MR method used in this study may be useful in early diagnosis of Parkinson’s disease. Limitations of this study include a small sample size and manual selection of the ROIs. Atlas-based or statistical mapping methods would be an alternative for an objective evaluation. More studies are necessary to validate the measurement methods for clinical use in diagnostics of early Parkinson’s disease.